Utilization of Plastic Waste and Rice Husk Ash in Polyethylene-Based Composites for Ceiling Applications - Gusti F. X. Wara Wangge; Yohanes Viva Servianus; Thadeus Rande (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2025)
This study aims to analyze the effect of polyethylene (PE) and rice husk ash (RHA) composition variations on the mechanical properties of recycled composites developed as environmentally friendly ceiling materials. Composite specimens were prepared through a systematic process involving shredding PE plastic waste into 3–5 mm particles, burning rice husks at 600–700 °C followed by sieving through a 200-mesh screen, melting the plastic at 160–170 °C, and mixing with RHA at three composition ratios: 80:20, 70:30, and 60:40 (PE:RHA). The mixtures were molded into 50 × 50 mm specimens and tested in accordance with ASTM D695 for compressive properties and ASTM D792 for density. The results show that composition variation significantly influences compressive strength, elastic modulus, and strain behavior. The 80:20 composition exhibited the highest elasticity, with a compressive strength of 15.59 MPa and an elastic modulus of 463.50 MPa; however, it fractured shortly after exceeding the elastic limit. The 60:40 composition achieved the highest compressive strength of 125 MPa with a strain of 56.6%, but showed brittle behavior due to its very low elastic modulus (7.5 MPa). The 70:30 composition demonstrated the most balanced mechanical performance, with a compressive strength of 61.65 MPa, a strain of 18.20%, and stable ductile behavior. Based on the overall mechanical performance, the 70:30 PE–RHA composition is recommended as the optimal formulation, as it provides the best balance between strength, stiffness, and deformation resistance. This composition is therefore considered the most suitable for non-structural ceiling applications requiring lightweight, mechanically stable, and environmentally sustainable materials.